2023
DOI: 10.1182/bloodadvances.2022007751
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between GPIb/IX antibodies, platelet hepatic sequestration, and TPO levels in patients with chronic ITP

Abstract: Immune thrombocytopenia (ITP) is an autoimmune bleeding disorder with an incompletely understood pathophysiology, but includes platelet-clearance in the spleen and liver via T-cells and/or platelet-autoantibodies. Strikingly, thrombopoietin (TPO) levels remain low in ITP. Platelet-glycoprotein (GP)Ibα has been described to be required for hepatic TPO generation, however, the role of GPIb-antibodies in relation to platelet hepatic sequestration and TPO-levels, with consideration of platelet counts, remains to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…The association between antiplatelet antibody and response to splenectomy is debated, impaired by heterogeneity in antibody testing and definition of response as well as by the low number of patients included in these retrospective series 6 . Recently, a retrospective study of 30 patients with ITP, positive antiplatelet antibody and indium‐labelled autologous platelet study (see below), demonstrated a slightly higher rate of splenic sequestration in case of the presence of anti‐GPIIb/IIIa (52.6%, n = 19) or anti‐GPV (52.6%, n = 19) antibodies than in case of the presence of anti‐GPIb/IX antibodies (37.5%, n = 16), 11 in line with the role of anti‐GPIIb/IIIa in splenic clearance of platelets and of anti‐GPIb/IX in hepatic clearance of platelets in ITP 12 …”
Section: Splenectomymentioning
confidence: 99%
“…The association between antiplatelet antibody and response to splenectomy is debated, impaired by heterogeneity in antibody testing and definition of response as well as by the low number of patients included in these retrospective series 6 . Recently, a retrospective study of 30 patients with ITP, positive antiplatelet antibody and indium‐labelled autologous platelet study (see below), demonstrated a slightly higher rate of splenic sequestration in case of the presence of anti‐GPIIb/IIIa (52.6%, n = 19) or anti‐GPV (52.6%, n = 19) antibodies than in case of the presence of anti‐GPIb/IX antibodies (37.5%, n = 16), 11 in line with the role of anti‐GPIIb/IIIa in splenic clearance of platelets and of anti‐GPIb/IX in hepatic clearance of platelets in ITP 12 …”
Section: Splenectomymentioning
confidence: 99%
“…An FCγR-independent pathway of platelet destruction is platelet desialylation. Studies have shown that GPIb/IX antibodies trigger platelet desialylation by recruiting neuramidase-1 to the plasma membrane [29]. Desialylated platelets are recognized by the Ashwell-Morell receptor expressed on hepatocytes, leading to their removal from circulation and to the production of TPO, a major growth factor of megakaryocytes [29].…”
Section: Mechanisms Of Peripheral Destructionmentioning
confidence: 99%
“…Danach werden sie präferenziell über Ashwell-Morell-Rezeptoren (AMR) in der Leber phagozytiert, ein Fc-Rezeptor-unabhängiger Abbauweg [22]. Während die Fc-Rezeptor-abhängige Phagozytose von Thrombozyten in der Milz vor allem bei anti-GP-IIb/IIIa-Antikörpern stattfindet (70-80 % der Fälle), ist die Leber-prädominante Sequestrierung von Thrombozyten insbesondere bei Antikörpern gegen das Glykoprotein Ibα (20-40 % der Fälle) beschrieben [23] und spricht schlecht auf Therapien an, die gegen die Fc-Rezeptoren der Makrophagen in der Milz gerichtet sind, wie z. B. Immunglobuline [24].…”
Section: Desialylierung Von Thrombozytenunclassified